2014
DOI: 10.1097/cej.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Relation of immune semaphorin/plexin signaling to carcinogenesis

Abstract: Semaphorins and plexins represent a highly conserved group of proteins that have recently been found to exert widespread regulatory functions outside the nervous system, including angiogenesis and immune regulation. Furthermore, these molecules are definitely implicated in the etiology of carcinogenesis and immune disorders. Their expression patterns and levels are deregulated in cancer cells and in cells of the tumor milieu. During the multistep development of cancer, its characteristic features include susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Semaphorin family members were initially characterized as axon-guidance factors with functions in axonal navigation, but have subsequently also been linked to the pathology of various diseases, such as cancer, immune disease and neurodegenerative disease ( Műzes and Sipos 2014 ; Neufeld and Mumblat 2016 ; Franzolin and Tamagnone 2019 ). Accumulated studies have shown that some semaphorins—including semaphorin 3E (SEMA3E), SEMA4D, SEMA5A, SEMA6D, and SEMA7A—play vital roles in tumorigenesis and tumor development by promoting angiogenesis and tumor-cell migration, as well as the epithelial-mesenchymal transition (EMT); in contrast, SEMA3A, SEMA3B, and SEMA3F exhibit tumor-inhibitory effects ( Neufeld et al, 2012 ; Neufeld and Mumblat 2016 ; Gurrapu and Tamagnone 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Semaphorin family members were initially characterized as axon-guidance factors with functions in axonal navigation, but have subsequently also been linked to the pathology of various diseases, such as cancer, immune disease and neurodegenerative disease ( Műzes and Sipos 2014 ; Neufeld and Mumblat 2016 ; Franzolin and Tamagnone 2019 ). Accumulated studies have shown that some semaphorins—including semaphorin 3E (SEMA3E), SEMA4D, SEMA5A, SEMA6D, and SEMA7A—play vital roles in tumorigenesis and tumor development by promoting angiogenesis and tumor-cell migration, as well as the epithelial-mesenchymal transition (EMT); in contrast, SEMA3A, SEMA3B, and SEMA3F exhibit tumor-inhibitory effects ( Neufeld et al, 2012 ; Neufeld and Mumblat 2016 ; Gurrapu and Tamagnone 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Semaphorin 6b (SEMA6B) is a member of the semaphoring axon-guidance family and was initially characterized as an axon guidance factor with axon navigation functions but has also been demonstrated to induce or inhibit tumor progression. The overexpression of this gene is related to colorectal cancer in humans [ 45 , 46 , 47 ]. ADORA2B encodes a protein belonging to the G protein-coupled receptor superfamily that plays a role in tissue distribution along with A1, A2A, and A3.…”
Section: Discussionmentioning
confidence: 99%
“…The VCRC GWAS in AAV identified a potential association of GPA with the gene SEMA6A (P = 2.09 × 10 −8 ) encoding the protein semaphorin 6A [7]. The function of the proteins belonging to this family is unclear, but it has been proposed that they may be involved in immune regulation [57]. The association between the rs26595 SNP of the SEM6A gene and GPA was recently investigated also in a different cohort of Northern European patients, including 879 GPA, 150 MPA and 191 EGPA [58].…”
Section: Other Associationsmentioning
confidence: 99%